2021
DOI: 10.1186/s12866-021-02180-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the spatial distribution and colony size was common for monogenetic bacteria in laboratory conditions

Abstract: Background Geographically separated population growth of microbes is a common phenomenon in microbial ecology. Colonies are representative of the morphological characteristics of this structured population growth. Pattern formation by single colonies has been intensively studied, whereas the spatial distribution of colonies is poorly investigated. Results The present study describes a first trial to address the questions of whether and how the spat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The value of Cor k was close to 1, which revealed that the area charged by the colony was highly positively correlated with the growth capacity of the colony. The results clearly demonstrated the generality of the Voronoi correlation ( Cor k ) in colony growth, which strongly supported our previous finding ( Xue et al, 2021 ) and indicated the commonly fair division of the space area for colony growth.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The value of Cor k was close to 1, which revealed that the area charged by the colony was highly positively correlated with the growth capacity of the colony. The results clearly demonstrated the generality of the Voronoi correlation ( Cor k ) in colony growth, which strongly supported our previous finding ( Xue et al, 2021 ) and indicated the commonly fair division of the space area for colony growth.…”
Section: Resultssupporting
confidence: 90%
“…To evaluate the effect of the spatial distribution on the growth of colonies, the spatial analysis was performed using the Voronoi diagram, a practical method to divide the multiple distributed points into regions, as reported previously ( Chacón et al, 2018 ; Xue et al, 2021 ). The parameter of the Voronoi area ( Vor i ) was calculated, indicating the space region on the plate assigned to the corresponding colony ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations